Influence of maintaining apical patency in post-endodontic pain - Snigdha Shubham; Manisha Nepal; Ravish Mishra; Kishor Dutta (BMC, 2021)
Abstract Background The concept of instrumentation beyond the apical foramen by small flexible file to prevent apical blockage is apical patency. However, this procedure might endow postoperative pain, thus to maintain apical patency or not is the matter of dilemma. Hence, the primary objective of this study was to compare postoperative pain between apical patency and non-patency groups and secondary objective was to evaluate the influence of number of visits, vitality of teeth, group of teeth and preoperative pain on post-operative pain. Methods Preselected (n = 178) patients based on group of teeth and status of pulp were randomly divided into 2 groups, apical patency and non-patency which was further treated in either single or multiple visits. After exclusion, 160 patients were included. Each group (n = 80) was subdivided in single visit (n = 40) and multiple visits (n = 40), including vital (n = 20) and non-vital teeth (n = 20) and single-rooted (n = 10) and multiple-rooted teeth (n = 10). Apical patency was maintained with a size 10 K-file during conventional hand filing step-back shaping procedure. Intensity of pain was recorded before treatment and on days 1, 2, and 7 after treatment using Numerical Rating Scale (NRS-11). Statistical analysis was done using Mann-Whitney U test, Spearman correlation and Multiple linear regression analysis. Results The primary outcome of this study showed statistically significant difference (p < 0.05) in postoperative pain scores between patency and non-patency groups with higher pain scores in patency group on 1st, 2nd and 7th day follow up. The secondary outcome showed postoperative pain in patency-maintained group was influenced by status of the pulp and preoperative pain only. Vital teeth of patency-maintained group treated in multiple visits showed statistically significant (p = 0.02) post-operative pain in day 1 follow up. Pre-operative pain showed positive correlation with postoperative pain with statistically significant difference. Conclusions Our study concluded that maintenance of apical patency increased postoperative pain. Evaluation of influence of number of visits, status of pulp, group of tooth and preoperative pain revealed status of pulp and preoperative pain as influencing factors for postoperative pain in patency group.